2019
DOI: 10.1037/cep0000175
|View full text |Cite
|
Sign up to set email alerts
|

Are figurative interpretations of idioms directly retrieved, compositionally built, or both? Evidence from eye movement measures of reading.

Abstract: Idioms are part of a general class of multiword expressions where the overall interpretation cannot be fully determined through a simple syntactic and semantic (i.e., compositional) analysis of their component words (e.g., kick the bucket, save your skin). Idioms are thus simultaneously amenable to direct retrieval from memory, and to an on-demand compositional analysis, yet it is unclear which processes lead to figurative interpretations of idioms during comprehension. In this eye-tracking study, healthy adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 71 publications
3
32
0
Order By: Relevance
“…However, this past work also revealed a general monolingual preference for adjacent VPCs overall, which we did not detect with bilinguals reading in their L1. This divergence is similar to the mismatch between current and early findings of classic idioms, more specifically related to the facilitative vs. interfering role of semantic transparency on reading (e.g., Titone et al, 2019). Indeed, the eye-tracking data from the present work indicates that L1 preferences emerge early on, during first pass reading, as opposed to emerging upon rereading.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…However, this past work also revealed a general monolingual preference for adjacent VPCs overall, which we did not detect with bilinguals reading in their L1. This divergence is similar to the mismatch between current and early findings of classic idioms, more specifically related to the facilitative vs. interfering role of semantic transparency on reading (e.g., Titone et al, 2019). Indeed, the eye-tracking data from the present work indicates that L1 preferences emerge early on, during first pass reading, as opposed to emerging upon rereading.…”
Section: Discussionsupporting
confidence: 66%
“…One could understand this pattern of results as evidence for a preferred direct meaning retrieval mechanism over word-by-word composition. When the VPC optimally matches what is likely stored in the lexicon (i.e., opaque, adjacent form) the meaning is retrieved quickly (Titone et al, 2019). However, when this mapping is less frequent or familiar, retrieval is less rapid, which aligns with recent work demonstrating that more figuratively-dominant idioms are read more quickly than idioms with more balanced figurative-literal meanings (Milburn and Warren, 2019).…”
Section: Experiments 1 Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the exact nature of the way in which decomposability modulates online processing is still disputed, as its effect is not always facilitatory. Titone and Libben (2014) found late inhibitory effects of decomposability in a cross-modal semantic priming task and Titone et al (2019) observed late inhibitory effects of decomposability during idiom reading. Interestingly, Westbury and Titone (2011) found an interaction of decomposability with age: in a literality judgment task, older adults were relatively slower than younger adults to accept non-decomposable idioms with a literal meaning and made more errors.…”
Section: Introductionmentioning
confidence: 98%